AB0406 Cardiovascular risk in rheumatoid arthritis: Are we aware?. (23rd January 2014) - Valls Roc, M.; Darnes, S.; Codina, O.; Sala, M.
Abstract : Background: patients with rheumatoid arthritis (RA) have a higher cardiovascular (CV) morbidity and mortality from accelerated atherosclerosis than the general population. The increased risk appears because of an increased prevalence of clasic CV risk factors (age, male gender, smoking, diabetes, obesity, hypertension, elevated total cholesterol and low HDL) and the inflammatory burden. Early and effective antirheumatic treatment, such as methotrexate and tumor necrosis factor-α blocking agents has been shown to be independently associated with lower CV risk. EULAR evidence-based recommendations for cardiovascular risk management published in 2009 advised determine CV risk assessment using national guidelines for all patients with RA. Objectives: determine CV risk in RA patients monitored in the Rheumatology section of county hospital. The reference area had a population of 130.000 inhabitants. Asses the relationship between the degree of RA activity and CV risk. Analyze the correlation between the drugs used to treat RA and CV risk. Methods: observational retrospective cohort pilot study. Patients had been recruited in rheumatology outpatient clinic. All patients fulfilled the 1987 RA criteria of the American College of Rheumatology. The aim is to determine the CV risk in patients with RA according to Framingham-REGICOR (F-REGICOR) and SCORE tables for european countries with low CV risk. Data was collected between January to June 2011 and included: age, sex, smoking, blood pressure (BP), total cholesterol and HDL, disease activity by DAS28 and drugs administered. Results: of 298 RA patients monitored in our center, only 38 (12.8%) had recorded enough variables to calculate CV risk. 17 men and 21 women, mean age 57.8±11.1 years. 7 patients smokers, 18.4% of the total. Mean systolic BP was 137.5 mmHg and diastolic BPof 76.9 mmHg. Mean total cholesterol was 208.4 mg/dl and HDL cholesterol of 53 mg/dl. Results of CV risk determinations according to F-REGICOR and SCORE are shown in table below. DAS28 had an average of 2.9 with SD 1.1. Linear regression analysis ruled out a significant association between DAS28 and CV risk. The drugs used by patients were: 58% NSAID, 60% corticosteroids, 63% methotrexate, 18% leflunomide and 32% biologics. There was no statistically significant differences between the different drug groups and each group of cardiovascular risk. Conclusions: we were able to determine CV risk in 12.8% of RA patients. Half of patients have low CV risk. Not found a significant association between cardiovascular risk and RA activity neither in relation to the drugs used. Disclosure of Interest: None Declared